2014
DOI: 10.3897/subtbiol.13.7256
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequences of troglobitic nicoletiid insects support Sierra de El Abra and the Sierra de Guatemala as a single biogeographical area: Implications for Astyanax

Abstract: The blind Mexican tetra fish, Astyanax mexicanus, has become the most influential model for research of cave adapted organisms. Many authors assume that the Sierra de Guatemala populations and the Sierra de El Abra populations are derived from two independent colonizations. This assumption arises in part from biogeography. The 100 m high, 100 m wide Servilleta Canyon of the Boquillas River separates both mountain ranges and is an apparent barrier for troglobite dispersion. Anelpistina quinterensis (Nicoletiida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Notably, many species of troglobites other than Astyanax inhabit caves spanning from southern El Abra to Sierra de Guatemala, and some were able to migrate among these areas within the last 12,000 years (Espinasa et al . 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, many species of troglobites other than Astyanax inhabit caves spanning from southern El Abra to Sierra de Guatemala, and some were able to migrate among these areas within the last 12,000 years (Espinasa et al . 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…Barriers for dispersal for aquatic and terrestrial organisms in the El Abra caves appear to be different. Espinasa et al (2014) sequenced the 16S rRNA of Anelpistina quinterensis (Nicoletiidae, Zygentoma, Insecta), a highly troglomorphic nicoletiid silverfish insect that inhabits from southern Sierra de El Abra to Sierra de Guatemala. Using a calibrated molecular clock, their data supports that this species migrated underground to reach both mountain ranges within less than 12,000 years, implying relatively easy underground migration, with no isolating evolutionary barrier for the central Sierra de El Abra, in terrestrial cave populations.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple authors (e.g. Bradic et al 2013;Gross 2012;Herman et al 2018) have suggested that each mountain range has independent evolutionary histories, although colonization independence has been disputed for the Sierra de Guatemala and Sierra de El Abra by Espinasa et al (2014). All cave localities (Molino, Caballo Moro, Jineo, Vásquez, and Escondido) involved in this study come from Sierra de Guatemala, with the exception of the Pachón and Tinaja cave populations, which are from Sierra de El Abra (Fig.…”
Section: Introductionmentioning
confidence: 98%